Secondary Bacterial Infection in Clinically Suspected Cases of Pulmonary Tuberculosis and Their Antibiotic Sensitivity Pattern - Shrestha, Rajani; Nayak, Niranjan; Jwarchan, Bishnu; Gauchan, Eva; Gokhale, Shishir (Nepal Medical College Journal, 2025)
Secondary bacterial infection has become one of the most important complications in patients suffering with pulmonary tuberculosis (PTB). The suppression of immunity, which can occur due to T-lymphocyte deficiency during active PTB disease, could be the main reason for the bacterial superadded infections. This aimed to evaluate tuberculosis (TB) status and secondary bacterial infections among them. A total of 400 sputum samples were collected and examined using Ziehl-Neelsen staining method as per revised national tuberculosis control program guidelines and GeneXpert following the WHO guidelines. Those sputum samples were also processed for routine bacterial culture and bacteria were identified by conventional techniques. Antimicrobial sensitivity testing was performed on Mueller-Hinton agar plates with commercially available antibiotic discs using Kirby-Bauer disc diffusion techniques and interpreted as per the guidelines of Clinical and Laboratory Standards Institute (CLSI). A total of 44 (11.0%) samples out of 400 yielded tuberculosis by GeneXpert assay and maximum positivity was noted among the age group 46-60 years (20.4%). The present study showed GeneXpert positivity for the MTB detected rate remained to be 11.0 % (44/400) detected as against smear positivity in only 7.5% (30/400) and this difference was found to be statistically significant (p<0.001). Overall, 220 (55.0%) secondary bacterial pathogens were isolated. Gram negative bacterial infection was most common. Of them, Klebsiella pneumoniae (33.63%; 74/220) was the commonest organism followed by Acinetobacter spp. (30%;66/220) and Pseudomonas aeruginosa (18%; 40/220). Streptococcus pneumoniae (6.36%; 14/220) was the commonest among the gram-positive bacteria. Majority (54.0%) of Klebsiella spp. showed resistance to Ciprofloxacin, while 29.7% Imipenem, 32.4% to Gentamicin, 35.13% to Piperacillin/Tazobactum, 37.8% to Amikacin. However, (70.0%) of Acinetobacter spp. showed resistance to Ciprofloxacin, while 75.7% were resistant to Ceftazimine, 54.5% Imipenem, 48.4% to Gentamicin, 31.0% to Amikacin. Interestingly, 44 of these 400 (11.0%) were found to positive be MTB by GeneXpert test and 220/400 (55.0%) bacterial infection and coinfection 22/44 (50.0%) among clinically suspected PTB cases. Tuberculosis remains a global threat despite effort to eradicate the disease and PTB co-infection with secondary bacterial infection may complicate the infection and treatment.